Cold War Legacy in Public and Private Health Spending in Europe - Jakovljevic, Mihajlo; Camilleri, Carl; Rancic, Nemanja; Grima, Simon; Jurisevic, Milena; Grech, Kenneth; Buttigieg, Sandra C. (Frontiers in Public Health, 2018)
Cold War Era (1946–1991) was marked by the presence of two distinctively different economic systems, namely the free-market (The Western ones) and central-planned (The Eastern ones) economies. The main goal of this study refers to the exploration of development pathways of Public and Private Health Expenditure in all of the countries of the European WHO Region. Based on the availability of fully comparable data from the National Health Accounts system, we adopted the 1995–2014 time horizon. All countries were divided into two groups: those defined in 1989 as free market economies and those defined as centrally-planned economies. We observed six major health expenditures: Total Health Expenditure (% of GDP), Total Health Expenditure (PPP unit), General government expenditure on health (PPP), Private expenditure on health (PPP), Social security funds (PPP) and Out-of-pocket expenditure (PPP). All of the numerical values used refer exclusively to per capita health spending. In a time-window from the middle of the 1990s towards recent years, total health expenditure was rising fast in both groups of countries. Expenditure on health % of GDP in both group of countries increased over time with the increase in the Free-market economies seen to be more rapid. The steeper level of total expenditure on health for the Free-market as of 1989 market economies, is due mainly to a steep increase in both the government and private expenditure on health relative to spending by centrally-planned economies as of the same date, with the out-of-pocket expenditure and the social security funds in the same market economies category following the same steepness. Variety of governments were leading Eastern European countries into their transitional health care reforms. We may confirm clear presence of obvious divergent upward trends in total governmental and private health expenditures between these two groups of countries over the past two decades. The degree of challenge to the fiscal sustainability of these health systems will have to be judged for each single nation, in line with its own local circumstances and perspectives.